1978
DOI: 10.1042/bst0061051
|View full text |Cite
|
Sign up to set email alerts
|

Ampholyte-Displacement Chromatography for the Separation of Serum Proteins

Abstract: The technique of ampholyte-displacement chromatography was first described for the separation of the isoenzymes of p-N-acetyl-D-hexosaminidase by Leaback & Robinson (1975). Subsequently we have used this technique for the separation of alpha-fetoprotein and albumin (Young &Webb, 1978). For both studies, complete separation could not be Vol. 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Displacement chromatography is a technique that has been successfully utilized for the enrichment and isolation of trace variants in peptide digests [9][10][11][12], as well as high-resolution separation of proteins [13][14][15][16], oligonucleotides [17,18] and small organic molecules [19,20]. As such, displacement chromatography provides a powerful but underutilized tool in the process development and characterization of complex biological therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Displacement chromatography is a technique that has been successfully utilized for the enrichment and isolation of trace variants in peptide digests [9][10][11][12], as well as high-resolution separation of proteins [13][14][15][16], oligonucleotides [17,18] and small organic molecules [19,20]. As such, displacement chromatography provides a powerful but underutilized tool in the process development and characterization of complex biological therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures for PSP lG it was previously noted that false high estimates are purification on a microgram scale were reported by obtained by this technique (8). The gel chromatography Young et al (19) and Engvall (20). Bohn et al ( ' 7) and, of the purified PSP lG was conducted utilizing 6 mol/L more recently, McFasthing et al (21) reported the of GuWCl as dissociating solvent, Both reduced and preparation of PSP lG in milligram quantities, sufficient samples demonstrated single for protein characterization and clinical studies.…”
Section: Fig 2 Polyacrylamide Gel Electrophoresis Of Purifiedmentioning
confidence: 99%